2012
DOI: 10.1007/s00423-012-0944-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic study and meta-analysis of C-reactive protein as a predictor of postoperative inflammatory complications after gastroesophageal cancer surgery

Abstract: There is limited evidence for the diagnostic accuracy of CRP levels for PIC after gastroesophageal cancer surgery. CRP levels on POD 4 might be useful to rule out PIC, but its diagnostic accuracy is moderate at best. For clinical routine use CRP levels are clearly not sufficient to predict PIC and have to be interpreted in the context of the whole clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 30 publications
6
85
1
2
Order By: Relevance
“…Interestingly, however, those two studies [19,31] were similar to our own in terms of the CRP cutoff value identified as the best predictor of postoperative infectious complications, which suggests that optimal predictive value of CRP was only minimally affected by differing amounts of surgical stress and varying incidences of postoperative morbidity in relation to the specific lesions being treated.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Interestingly, however, those two studies [19,31] were similar to our own in terms of the CRP cutoff value identified as the best predictor of postoperative infectious complications, which suggests that optimal predictive value of CRP was only minimally affected by differing amounts of surgical stress and varying incidences of postoperative morbidity in relation to the specific lesions being treated.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, the sample size of the present study, at 417 patients, is currently the largest in the literature on esophagogastric cancer surgery [19,31], as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations